Ingestion of microplastics and textile cellulose particles by some meiofaunal taxa of an urban stream. (January 2023) - Di Lorenzo, Tiziana; Cabigliera, Serena Benedetta; Martellini, Tania; Laurati, Marco; Chelazzi, David; Galassi, Diana Maria Paola; Cincinelli, Alessandra
Abstract: Microplastics (MPs) and textile cellulose are globally pervasive pollutants in freshwater. In-situ studies assessing the ingestion of MPs by freshwater meiofauna are few. Here, we evaluated MP and textile cellulose ingestion by some meiofaunal taxa and functional guilds of a first-order stream in the city of Florence (Italy) by using a tandem microscopy approach (fluorescence microscopy and μFTIR). The study targeted five taxa (nematodes, oligochaetes, copepods, ephemeropterans and chironomids), three feeding (scrapers, deposit-feeders, and predators), and three locomotion (crawlers, burrowers, and swimmers) guilds. Fluorescent particles related to both MPs and textile cellulose resulted in high numbers in all taxa and functional guilds. We found the highest number of particles in nematodes (5200 particles/ind.) and deposit-feeders (1693 particles/ind.). Oligochaetes and chironomids (burrowers) ingested the largest particles (medium length: 28 and 48 μm, respectively), whereas deposit-feeders ingested larger particles (medium length: 26 μm) than scrapers and predators. Pellets were abundant in all taxa, except for Chironomidae. Textile cellulose fibers were present in all taxa and functional guilds, while MP polymers (EVA, PET, PA, PE, PE-PP) differed among taxa and functional guilds. In detail: EVA and PET particles were found only in chironomids, PE particles occurred in chironomids, copepods and ephemeropterans, PA particles were found in all taxa except in nematodes, whereas particles made of PE-PP blend occurred in oligochaetes and copepods. Burrowers and deposit-feeders ingested EVA, PET, PA, PE and PE-PP, while crawlers and scrapers ingested PE and PA. Swimmers and predators ingested PE, PA and PE-PP. Our findings suggest a pervasive level of plastic and textile cellulose pollution consistent with an urban stream which propagates in the meiofaunal assemblage of the stream ecosystem. Graphical abstract: Image 1 Highlights: We gathered evidence of MP ingestion by meiofauna of an urban stream. The number, size, shape and type of MPs varied among the meiofaunal taxa. Deposit-feeders showed the highest number of particles/ind. The largest particles were ingested by burrowers. Burrowers/deposit-feeders ingested the highest number of MP polymers.